Ensino de ciências por investigação: um desafio à formação dos professores dos anos escolares iniciais - SOARES, Gilma Favacho Amoras (Universidade Federal do Pará, 2019)
This is a formation research, of a qualitative nature, in the narrative modality, organized in formative meetings, which I call formation forums, as contributions for the continued formation of teachers in the teaching practice in the initial school years, for the teaching of sciences through. Of investigative practices. The teacher´s role in this teaching proposal is to encourage questioning, argumentation, communication, to lead questions, to stimulate and to propose challenges to oneself and the students. The scenario for this research is a school from the state system, where I have been working for 12 years. The motivation to do it comes from my concern as a trainer teacher, from the observation in my practice that the participating teachers taught Sciences based mainly on the contents presented in the didatic books, which led me to believe that it would be important to provide discussions, starting on a reflexive teaching proposal that put the student as the subject of his own learning. I proposed to them a formative collaborative work, which I intend to know, in what terms the teacher´s formation in the School, from the teaching by investigation, contributes to the teacher´s formation who teaches sciences in the initial years. This research involved three teachers who taught, at that moment, for the 3rd, 4th and 5th years. I used as instruments for data processing: questionnaire, interview, field diary, audio recordings, individual and collective productions.We observed that from the discussions in the formation forums, teachers attributed new meanings to their practices in the classroom, starting to propose teaching activities through investigative practices, providing active participation of students in the construction of knowledge and showing themselves more satisfied with the own teaching practice. Therefore, the research in question is relevant, because it invests in the realization of formation forums, providing the teachers of a Public School, innovation in their practices by encouraging students to participate in their own learning. In the course of the formation forums, I watched teachers involved in the context of the discussions, signaling "openness" to changes in their work. The Continuous formation contributed with the subject to advance in the process to building of knowledge and development personal and professional that evidenced in the narratives of the subjects, in the moment that they expressed changes in the way they see, feel, think and express themselves, in face of confirmation of a nonconformity feeling provoked during the continuous formation lived in the context of the school. Encased at this dissertation is found a video prepared with the participating teachers that contains the formation research procedures, in general terms, and the reported learning by them during the Continuous formation process, focus of this research.